Estimated Impact of Contextual Variables on Academic Achievement among Students in Baja California - Mauricio Carvallo Pontón; Joaquín Caso Niebla; Luis Ángel Contreras Niño (Universidad Autónoma de Baja California, 2007)
In the following article, the effects of diverse variables are analyzed contextually in the educational achievement on a sample of 1,817 students of the sixth grade of elementary school and 1,239 of third year of high school of Baja California, who responded to the National Tests offered by the National Institute for the Evaluation of the Education in 2004. The results observed are consistent with the reported in most of the national and international literature: the women present better performance than the men in reading comprehension, and the men register better performance in math; the students with ages over the ones that correspond to the sixth grade of elementary school or third year of secondary school, present lower performance levels to those of their schoolmates; the students of the morning shift present higher performance levels compared to the evening shift students; and the students of private schools present better results than those of public schools. It was also analyzed, through hierarchical lineal models, the effect of the socioeconomic level of the context of the school and of the professor in the educational achievement. In all the cases, the levels of variance explained turned out to be smaller that the registered in other similar national studies.